Rehabilitating of used Generator Oil by Acid /Bentonite Treatment and Studying of its Performance Evalution - Khudhair, Muna Mahmood; Abas, Kafaa Fadhil; Hameed, Taghreed Mahdi; Assad, Awali; Nifal, Wasan (Journal of Petroleum Research and Studies, 2014)
Used generator lubricant oils are considered hazardous wastes because of their high content of pollutants (thermal degradation products from the base oil and combustion products from fuel and lubricant and external pollutants). Thus, this research aimed to refining the waste oils for economic and environmental purpose. In this study, it was applied acid / bentonite treatment which include treatment with commercial sulphuric acid followed by adsorption on Iraqi bentonite and study the effect of treated used genarator oil and regards to enhancing their performance in service. The quality checked by evaluation of some important properties i.e. specific gravity, viscosity, flash point, pour point, ash content, and total acid number. The results of treated used oil showed that, specific gravity decreased from 0.898 to 0.894, viscosity increased from 95 cst to 136 cst. ,flash point increased from 179 oC to 200 oC, pour point increased from -13 oC to -16 oC, ash content decreased from 1.174 %to, 1.0775% and total acid number decreased from 2.983mg KOH/g to1.0775mg KOH/g. The results of evaluation of performance of fresh and treated generator oil studied by comparison of some properties such as specific gravity, viscosity, flash point pour point, ash content, and total acid number to the oils in use.